2008
DOI: 10.1007/s00213-008-1076-0
|View full text |Cite
|
Sign up to set email alerts
|

Discriminative stimulus effects of the cannabinoid CB1 receptor antagonist rimonabant in rats

Abstract: Objective-To examine the discriminative stimulus effects of the cannabinoid CB 1 receptor (CB 1 R) antagonist/inverse agonist rimonabant (SR141716A) using a discriminated taste aversion (DTA) procedure.Materials and methods-Groups of rats were trained to discriminate between drug (5.6 or 3 mg/kg) and vehicle in DTA (t′=20 min). The 30-min drinking opportunity after rimonabant pretreatment was followed by injection of lithium chloride (120 mg/kg) in the experimental (EXP) animals. When offered fluid after vehic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 51 publications
2
15
0
Order By: Relevance
“…As before (Järbe et al 2001), surmountable antagonism for mAEA/rimonabant combinations did not occur. Such tests were accompanied by reduced rates of responding (see also Järbe et al 2003bJärbe et al , 2008. It is possible that route of administration may play a role as Solinas et al (2007a) observed a limited shift to the right of the mAEA generalization curve when increasing doses of the drug were administered intravenously following pre-treatment with i.p.-administered rimonabant (3 mg/kg).…”
Section: Discussionmentioning
confidence: 99%
“…As before (Järbe et al 2001), surmountable antagonism for mAEA/rimonabant combinations did not occur. Such tests were accompanied by reduced rates of responding (see also Järbe et al 2003bJärbe et al , 2008. It is possible that route of administration may play a role as Solinas et al (2007a) observed a limited shift to the right of the mAEA generalization curve when increasing doses of the drug were administered intravenously following pre-treatment with i.p.-administered rimonabant (3 mg/kg).…”
Section: Discussionmentioning
confidence: 99%
“…Acquisition was demonstrated by consistently low levels of drinking in the presence of rimonabant and high levels of drinking in its absence (as compared to rats that received the same schedule of rimonabant and vehicle injections, but did not receive lithium chloride). Results of substitution tests in the discriminating rats showed that rimonabant and its diarylpyrazole analog AM-251 substituted whereas CB 2 receptor antagonists, SR144528 and AM630, did not [115]. Δ 9 -THC also failed to substitute for rimonabant when administered alone; however, when administered in combination with rimonabant, it attenuated rimonabant's suppression of drinking, suggesting opposing actions at the CB 1 receptor [115,116].…”
Section: Cannabinoid Antagonist Discriminationmentioning
confidence: 90%
“…Results of substitution tests in the discriminating rats showed that rimonabant and its diarylpyrazole analog AM-251 substituted whereas CB 2 receptor antagonists, SR144528 and AM630, did not [115]. Δ 9 -THC also failed to substitute for rimonabant when administered alone; however, when administered in combination with rimonabant, it attenuated rimonabant's suppression of drinking, suggesting opposing actions at the CB 1 receptor [115,116]. Hence, rimonabant appears to be discriminable, but only under modified experimental conditions.…”
Section: Cannabinoid Antagonist Discriminationmentioning
confidence: 95%
See 1 more Smart Citation
“…As was found with sibutramine, rimonabant produced an average placebo-subtracted weight loss of less than 5% (Pi-Sunyer et al 2006). Rimonabant has been shown to produce discriminative stimulus effects using a discriminated taste avoidance procedure (Järbe et al 2004(Järbe et al , 2008, and rimonabant antagonizes the discriminative stimulus effects of THC and other CB 1 agonists (Järbe et al 2001;Mansbach et al 1996;Wiley et al 1995a, b).…”
Section: Introductionmentioning
confidence: 91%